Helping teachers teach : a school library media specialist's role - Turner, Philip M., 1948-; Riedling, Ann Marlow, 1952- (Westport, CT : Libraries Unlimited, 2003)
Examines the role of the school library media specialist as an instructional consultant, and examines each step of the instructional design process.
Includes bibliographical references and index.
Reference and Research Book News.
School Library Journal.
Professional
Keywords: Curriculum planning -- United States; Instructional materials centers -- United States; Libraries and education -- United States; Libraries and teachers -- United States; Media programs (Education) -- United States; School libraries -- United States; Curriculum planning -- United States; Educational technology -- United States; Instructional materials centers -- United States; Libraries and education; Libraries and teachers; School libraries -- United States